Court and spark - Nelson, Sean (Continuum, 2007)
An analysis of folk-singer Joni Mitchell's album Court and spark and its place within the body of her work.
Keywords: Mitchell, Joni / Court and spark; Mitchell, Joni -- Court and spark; Mitchell, Joni -- 1943- -- Court and spark